Estimation of consolidation settlement of fibrous peat [compact disc] - 309908 Bong, Ting Ting (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006